Spatio‐temporal Keyframe Control of Traffic Simulation using Coarse‐to‐Fine Optimization - Han, Yi; Wang, He; Jin, Xiaogang (Computer graphics forum, 2022)
We present a novel traffic trajectory editing method which uses spatio‐temporal keyframes to control vehicles during the simulation to generate desired traffic trajectories. By taking self‐motivation, path following and collision avoidance into account, the proposed force‐based traffic simulation framework updates vehicle's motions in both the Frenet coordinates and the Cartesian coordinates. With the way‐points from users, lane‐level navigation can be generated by reference path planning. With a given keyframe, the coarse‐to‐fine optimization is proposed to efficiently generate the plausible trajectory which can satisfy the spatio‐temporal constraints. At first, a directed state‐time graph constructed along the reference path is used to search for a coarse‐grained trajectory by mapping the keyframe as the goal. Then, using the information extracted from the coarse trajectory as initialization, adjoint‐based optimization is applied to generate a finer trajectory with smooth motions based on our force‐based simulation. We validate our method with extensive experiments.